Pengaruh Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Toraja Utara - Tarima, Asyer Lunda'; Bandhaso, Mira La'bi; Baharuddin, Baharuddin (Politeknik Negeri Ambon, 2025)
This research aims to determine the significant influence of work motivation on employee performance at the North Toraja Regency Population and Civil Registration Service Office. The population in this study were employees who worked at the North Toraja Regency Population and Civil Registration Service Office. The number of samples in this study was 39 people from the entire population. Sampling was carried out by providing written statements or questions to respondents who worked at the Population and Civil Registration Service Office of North Toraja Regency so that they could be answered. The data analysis used is analysis, correlation coefficient (r), coefficient of determination (r²), and T test. The correlation coefficient test (r) results produce a value of 0.692. The coefficient of determination test results (r²) produced a 47.8 or 48% value. This shows that work motivation (X) has a 48% influence on employee performance (Y), while other factors influence the rest. From the results of the t_count and t_count tests above, it can be seen that the t_count value is 5.821, so t_count > t_table. So, this shows that work motivation (X) significantly affects employee performance (Y). Keywords: Work Motivation, Employee Performance.